Is line-source modeling suitable for ultraviolet light application in an air cleaner duct? - Li, Peiyang; Koziel, Jacek A.; Yedilbayev, Bauyrzhan; Paris, Reid Vincent; Walz, William B.; Ramirez, Brett C. (Frontiers in Built Environment, 2024)
Ultraviolet-C (UV-C) germicidal light can effectively inactivate airborne pathogens and mitigate the transmission of infectious diseases. As the application of UV-C for disinfection gains popularity, practical estimation of UV irradiance is essential in determining the UV fluence (dose) and designing tubular UV lamp configurations for indoor air treatment. It is generally understood that the inverse square (~1/d 2 ) law (i.e., irradiance is proportional to the inverse square of the distance) applies well to point light sources. However, there has been a recognition that the ~1/d 2 law does not work well for tubular light sources in the commonly defined near-field applications where the UV source is relatively close to the treated air. Therefore, practical near-field irradiation estimation is needed for designing portable air cleaners and heating, ventilation, and air conditioning (HVAC) ducts with built-in UV light bulbs. This research investigated UV-C light irradiance from tubular (L = 0.9 m) light bulbs at near distances inside an air cleaner prototype duct under three power output (1-, 4-, and 8-bulb) scenarios and conducted theoretical estimation based on a line-source irradiation model. Similarly sized visible fluorescent bulbs were used as a reference. The data were fitted on both ~1/d 2 and ~1/d correlation of irradiance with distance. Both measured and line source estimated data fit better (i.e., evaluated by R-square, standard errors, root mean squared errors) with the ~1/d than the ~1/d 2 relationship in the near distance. Although the differences between the measured and the modeled were observed, the pattern of light distribution generally follows an inverse relationship (~1/d) with distances (d) shorter than two tubular bulb lengths (d < 2L). The pattern applies to both UV and visible light tested in this study. It is recommended that the inverse (~1/d) correlation be used for near-distance estimation of light distribution, especially for disinfection purposes in air ducting for indoor air quality improvement and airborne disease mitigation.